Clinical significance of serum retinol binding protein‐4 levels in patients with systemic sclerosis. (26th December 2011) - Toyama, T.; Asano, Y.; Takahashi, T.; Aozasa, N.; Akamata, K.; Noda, S.; Taniguchi, T.; Ichimura, Y.; Sumida, H.; Tamaki, Z.; Masui, Y.; Tada, Y.; et al.
Abstract Background Retinol binding protein‐4 (RBP‐4) is a member of adipocytokines, which is potentially associated with fibrosis, vasodilation, and angiogenesis in addition to insulin resistance. Objective To investigate the clinical significance of serum RBP4 levels in patients with systemic sclerosis (SSc), which is a systemic autoimmune disease characterized by fibrosis and vasculopathy. Methods Serum RBP4 levels were determined by enzyme‐linked immunosorbent assay in 62 SSc patients and 19 healthy controls. Results Similar to patients with chronic kidney disease, serum RBP4 levels inversely correlated with estimated glomerular filtration rate in SSc patients with renal dysfunction. Therefore, analyses were carried out by excluding SSc patients with estimated glomerular filtration rate <60 mL/min/1.73 m2. Serum RBP4 levels were significantly lower in diffuse cutaneous SSc (dcSSc) than in control subjects [median (25–75 percentile); 25.8 μg/mL (19.6–47.0) vs. 43.1 μg/mL (31.7–53.4), P < 0.05], while there was no significant difference between limited cutaneous SSc (lcSSc) [28.0 μg/mL (25.4–43.3)] and control subjects. In both of dcSSc and lcSSc, patients with Raynaud's phenomenon had RBP4 levels significantly lower than those without. Furthermore, serum RBP4 levels inversely correlated with pulmonary function test results in dcSSc and with right ventricular systolic pressure in lcSSc. Conclusion Decreased RBP4 levels are associated with the prevalence of Raynaud's phenomenon in dcSSc and lcSSc, with the severity of interstitial lung disease in dcSSc, and with the degree of pulmonary vascular involvement in lcSSc, suggesting the possible contribution of RBP4 to the pathological events in this disorder.